Penerapan Algoritma Kruskal Pada Jaringan Kabel di Tanjung Selor - dady sulaiman (Universitas Pendidikan Ganesha, 2021)
Graph theory is a branch of mathematics that has actually existed for more than two hundred years. In everyday life, there are problems regarding optimization that can be solved using a minimum spanning tree, otherwise known as the Minimum Spanning Tree. Kruskal's algorithm is a method used to find and form a minimum spanning tree. The purpose of this research is to obtain the minimum value of a cable network at PT. Telkom Tanjung Selor. The results of the optimal calculation using Kruskal's Algorithm assisted with Maple produce minimum spanning trees with a weight of m compared to the initial value of m. Thus, PT. Telkom Tanjung Selor can save cables as long as m from the total length of the cable installed.